The role of ultraviolet radiation and tyrosine stimulated melanogenesis in the induction of oxidative stress alterations in fair skin melanocytes - Baldea, I.; Mocan, T.; Cosgarea, R. (Experimental Oncology, 2009)
Melanocytes are producing melanin after UV irradiation as a defense mechanism. However, UV-induced damage is involved in melanoma initiation, depending on skin phototype. Melanocytes seem to be extremely susceptible to free radicals. Their main enzymatic antioxidants are superoxide dismutase and catalase. Aim: To study how melanin synthesis modulates the activity of the oxidative stress defense enzymes and cell proliferation after UV induced cell damage. Methods: Normal human melanocyte cultures from fair skin individuals were exposed to high levels of L-tyrosine and irradiated, with 20, 30, 40 mJ/cm2 UVA, and respective UVB. Proliferation was measured using a MTS assay; viability was assessed by trypan blue exclusion dye method. Spectrophotometrical methods were used to determine total melanin content, the enzymatic activity of tyrosinase, superoxide dismutase and catalase. Results: Tyrosine had a negative effect on proliferation, enhanced with time elapsed. Overall, UV irradiation decreased proliferation. UVA increased proliferation relative to UVB in the cultures exposed for a longer time to high (2 mM) tyrosine concentration. There were no proliferation differences between UVA and UVB irradiation in lower tyrosine concentration exposed melanocytes. Both, UV irradiation and tyrosine increased melanogenesis. Exposure of the melanocytes to increased levels of tyrosine in medium (0.5 mM and 1 mM) and UV irradiation enhanced the activity of superoxide dismutase and catalase. The enzymes showed a high activity rate in melanocytes while exposed for a short time to 2 mM tyrosine, but their activity was dramatically decreased with longer tyrosine exposure and UV irradiation. Conclusion: Our data indicate that in low phototype melanocytes, melanogenesis, either following UV irradiation, or tyrosine exposure, especially in high concentrations, was detrimental for the cells by reducing the activity of catalase and superoxidedismutase, the natural antioxidants. UVA was more efficient in stimulating the activity of superoxide dismutase and catalase but also in depleting the reserves of the enzymatic defense against oxidative stress, especially catalase, than UVB. This physiologic response to UV light can be considered as an adjunctive risk factor for people with low phototype for developing a melanoma, when exposed to UV irradiation.